Elegy of Sorrow: The Experience of Grief for Individuals Who Have Lost Family Members Due to COVID-19 - Louisa, Aurora; Astuti, Kamsih (Bulletin of Counseling and Psychotherapy, 2024)
The COVID-19 pandemic has caused grief among individuals due to restrictions on communication, end-of-life care, deceased remains management, and mourning customs. This research aimed to understand the individual process of undergoing grief following the loss of a family member. The study involved four participants who experienced the loss of a core family member, along with an informant. The research found that COVID-19's constraints, intimacy, psychological resilience, coping capacity, death anticipation, and social support influenced participants' grieving processes. Loss triggers physical, emotional, and communal distress, forcing family members to fulfill vacated roles. Despite grief, individuals can adjust and persevere, bringing novel perspectives and enhanced understanding of life. The study's findings reveal that the passing of a family member due to COVID-19 evoked distinct responses in each participant, and those who have experienced such loss express optimism that increased community awareness can prevent others from experiencing similar ordeals.